Biomechanics, anatomy, pathology, imaging and clinical evaluation of the acetabular labrum: current concepts. Issue 3 (2nd May 2018) - Hartigan, David E; Perets, Itay; Meghpara, Mitchell B; Mohr, Mitchell R; Close, Mary R; Yuen, Leslie C; Domb, Benjamin G
Abstract : The labrum has been recognised to play an important role in the hip in regard to stability, fluid regulation, decreasing contact forces, proprioception and nociception. These functions are all important for normal joint homeostasis in a well-functioning hip and can be responsible for increasing joint pain, damage, instability and dysfunction when compromised. The labrum has been studied intently in the last few decades to better understand its role in the normal and the pathologic hip and how best to treat pathology that causes debilitating hip pain and dysfunction. This current concept review discusses and summarises the current literature on labral anatomy, biomechanics, pathology, clinical exam and imaging.